Integrating CUDA memory management mechanisms for domain decomposition of an acoustic wave kernel implemented in OpenMP - Freire, Yuri Nicolau; Senger, Hermes (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2023: Anais da XIV Escola Regional de Alto Desempenho de São PauloDO - 10.5753/eradsp.2023.231895, 2023)
OpenMP is a well-known tool for parallelizing code in a directive-based programming model. While it has been extended to include support for offloading for devices such as GPUs, multi-gpu programming using data map directives requires redundant data allocation and non-intuitive data synchronization. This paper studies an alternative implementation of a CUDA-OpenMP hybrid kernel using native Unified Virtual Addressing memory pointers in an OpenMP target kernel.